La longue histoire de la recherche sur les aqueducs romains de Lyon - Jean Burdy (Gallia)
“The long history of research on Lyon’s Roman aqueducts (France)” is presented here in four stages from the 18th century to the present day. Each stage is marked by a leading figure in the world of archaeology, by the efforts of the Académie des sciences, belles-lettres et arts de Lyon, and today by the involvement of professional archaeologists.